Factors Related to the Recurrence of Low-grade Gliomas - Lin, David Ilun Tseng [UNESP]; Muhlmann, Lindson [UNESP]; Botta, Fabio Pires [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP]; Zanini, Marco Antonio [UNESP]; Fernandes, Adriano Yacubian [UNESP] (Georg Thieme Verlag Kg, 2023)
Objective To identify the determining factors for reoperation in patients with lowgrade gliomas, taking into account the degree of resection, and to analyze the histological aspects, observing possible transformations with signs of malignancy in the tissue samples.Materials and Methods The sample consisted of 40 cases of low-grade glioma that were operated on at Hospital das Cl & iacute;nicas de Botucatu between 2013 and 2019.Results The mean follow-up was of 37 months, and the sample was composed of 28 men and 12 women with a mean age at the first surgery of 43.1 +/- 15.6 years. Epileptic seizures were observed in 31 (77.5%) patients. According to the histological classification, half of the patients presented oligodendroglioma (50%), of grade II in most cases (97.5%). Total or subtotal resection was achieved in 22 (55%) patients. Only one patient underwent radiotherapy, and two underwent chemotherapy. Reoperation was performed in 20 (50%) patients. The median interval between the first surgery and the reapproach was of 16 (range: 0-77) months. In the second approach, the histological classification was of astrocytoma in 4 (20%) cases, oligoastrocytoma in another 4 (20%), oligodendroglioma in 7 (35%), and glioblastoma in 5 (25%) cases. The only variable associated with the need for reoperation was the degree of resection after the first surgery (p = 0.013).Conclusions Total resection of low-grade gliomas, when feasible, should be performed to avoid recurrence.
Keywords: gliomas; low grade; microsurgery; baixo grau; microcirurgia